Progressive muscle relaxation is effective in preventing and alleviating of chemotherapy-induced nausea and vomiting among cancer patients: a systematic review of six randomized controlled trials - Tian, Xu; Tang, Rong-Ying; Xu, Ling-Li; Xie, Wei; Chen, Hui; Pi, Yuan-Ping; Chen, Wei-Qing (Supportive care in cancer, 2020)
Purpose Previous systematic review suggested a beneficial effect of progressive muscle relaxation (PMR) for cancer patients receiving chemotherapy. However, poor quality of eligible studies which included in previous systematic review impaired the reliability and validity of findings. The aim of the present systematic review was to further assess the value of PMR in chemotherapy-induced nausea and vomiting. Methods We assigned two independent investigators to search potential studies in PubMed, Cochrane Controlled Register of Trial (CENTRAL), Cumulative Index to Nursing and Allied Health Literature (CINAHL), China Biomedical Literature database (CBM), China National Knowledge Infrastructure (CNKI), and Wanfang Data database. We used data extraction sheet to extract essential information, and used the Cochrane risk of bias assessment tool to appraise the quality of eligible studies. Finally, we qualitatively summarized the results of all included studies. Results Six studies enrolling 288 patients were included finally. Of these 6 studies, three were labeled as moderate quality and the remaining studies were low quality. All included studies consistently suggested that PMR has a positive effect on chemotherapy-induced nausea and vomiting, especially on the incidence, frequency, and degree of delayed nausea and vomiting. Conclusion Independent studies indicated that PMR was a beneficial approach of preventing and alleviating chemotherapy-induced nausea and vomiting among cancer patients. However, further studies enrolling other types of primary tumors should be designed in order to increase the generality of PMR because studies which were included in the present systematic review mainly considered patients with lung cancer and breast cancer. Moreover, future studies with high quality and large-scale are also warranted in order to address the limitations in the present systematic review such as poor quality and limited data of eligible studies.